AI Bias for Creative Writing: Subjective Assessment Versus Willingness to Pay - Martin Abel; Reed Johnson (Institute of Labor Economics (IZA), 2025)
How do perceptions of AI versus human authorship affect engagement with creative work? In an incentivized experiment, participants (N=654) assessed the content of a short story labeled as either human or AI-generated and reported their willingness to pay and work to finish reading it. Consistent with prior research, the AI-labeled story received significantly lower content assessments. However, the time people invest in reading the story and their willingness to pay and work did not differ between the labels, even for the 36% of participants who profess to value human over AI writing. These findings raise questions about whether subjective assessments and aspirations to favor human authorship translate into actions.
Keywords: D12; O33; Z11; 330; Artificial Intelligence; creative writing; willingness to pay; AI bias